Isolation of a new cytotoxic colchinoid from Gloriosa superba roots - Goel B.; Reddy H.; Cholkar A.; Kumar S.; Guru S.K.; Jain S.K. (My University, 2025)
A new colchinoid compound, identified as N-deacetyl-N-formylcornigerine (1), named glorigerine was isolated from the roots of Gloriosa superba, along with two known compounds. The structures of isolated compounds were elucidated by 1 D and 2 D NMR and HRMS experiments. Glorigerine (1) differed from cornigerine (6) by the presence of an N-formyl group instead of the N-acetyl group. Glorigerine (1) was found to have moderate cytotoxicity when tested against four human cancer cell lines. © 2022 Informa UK Limited, trading as Taylor & Francis Group.